O13 Pregnancy vitamin D supplementation leads to greater offspring bone mineral density at 4 years: the MAVIDOS randomised placebo controlled trial. (20th April 2020) - Curtis, Elizabeth M; Moon, Rebecca J; D'Angelo, Stefania; Crozier, Sarah R; Bishop, Nicholas J; Gopal- Kothandapani, Sujatha; Kennedy, Stephen; Papageorghiou, Aris T; Fraser, Robert; Gandhi, Saurabh V; Schoenmakers, Inez; Prentice, Ann; et al.
Abstract: Background: Observational studies have demonstrated associations between maternal gestational vitamin D status and offspring bone health. We have recently shown, in a randomised controlled trial, that pregnancy vitamin D supplementation leads to improved offspring bone mass at birth amongst winter deliveries (when background 25(OH)-vitamin D levels are lowest). In the present analysis, we aimed to evaluate whether the beneficial effect of pregnancy vitamin D supplementation on neonatal bone mass is sustained into early childhood, with bone indices assessed at age 4 years in a subset of participants of the MAVIDOS trial. Methods: Pregnant women were randomised in Southampton, Oxford and Sheffield, in a double-blind design, to 1000 IU/day cholecalciferol or matched placebo from 14 weeks' gestation to birth. At 4 years of age (Southampton participants only, n = 723 births), offspring assessments included anthropometry, whole-body dual-energy x-ray absorptiometry (DXA) [Hologic Horizon, yielding whole body less head (WBLH) bone mineral content (BMC), bone mineral density (BMD), bone area (BA) and lean mass (LM)], and a maternal questionnaire. Linear regression was used to estimate the mean difference (represented by β) in outcomes between the two randomisation arms, adjusted for sex and age at DXA. Further models were additionally adjusted for gestational age, maternal BMI, and child's sedentary time. All outcomes were standardised to a standard deviation scale, for ease of comparison. Full ethics and MHRA approvals were granted. Results: 564 children attended the 4-year visit; 452 had a useable DXA with minimal movement artefact. Maternal pregnancy vitamin D supplementation led to greater offspring indices of bone mass compared with placebo, irrespective of season. For example, WBLH BMD at age 4 years was greater in the offspring of supplemented mothers [β = 0.18 SD (95%CI: 0.00, 0.35), p = 0.047]; there was also evidence of greater LM in the intervention group [β = 0.15 SD (95%CI: -0.02, 0.31), p = 0.081]. In fully adjusted models associations were consistent for lumbar spine indices and for BA and BMC. In keeping with the offspring findings, maternal vitamin D supplementation led to significantly higher maternal plasma 25(OH)D concentrations in late pregnancy (34 weeks' gestation): placebo group (median(IQR)): 42.4 nmol/l (23.3, 56.4); vitamin D group: 67.4 nmol/l (56.2, 80.3); p < 0.001. Conclusion: This is the first ever demonstration in a large placebo-controlled, double-blind randomised controlled trial that maternal pregnancy vitamin D supplementation leads to improved bone and lean mass in children. Our findings suggest that maternal cholecalciferol supplementation may have lasting benefits for offspring musculoskeletal health and thus represent an important public health message. This work was supported by grants from Versus Arthritis 17702, Medical Research Council (MRC #405050259; #U105960371), Bupa Foundation, NIHR Southampton Biomedical Research Centre (BRC), University of Southampton, and NIHR Oxford BRC, University of Oxford. EC was supported by the Wellcome Trust (#201268/Z/16/Z). Disclosures: E.M. Curtis None. R.J. Moon None. S. D'Angelo None. S.R. Crozier None. N.J. Bishop None. S. Gopal- Kothandapani None. S. Kennedy None. A.T. Papageorghiou None. R. Fraser None. S.V. Gandhi None. I. Schoenmakers None. A. Prentice None. H.M. Inskip None. K.M. Godfrey None. K. Javaid None. R. Eastell None. C. Cooper None. N.C. Harvey None.